Reranan Kepemimpinan Terhadap Usaha Peningkatan Produktivitas Kerja Karyawan Pada PT Bukaka Teknik Utama Tbk. (Divisi Garbarata) - Zuhdi, Saefudin; Nuryana, Rus (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2002)
Firmâs leader has important roles in increasing workersâ productivity. From the result of linear analysis and by virtue of homogeneity test, itâs stated that if the leader do his work wellâ workersâ productivity will be up raised. This regard was proved by PT Bukaka Teknik Utama tbk. Garbarata division. Increase in productivity reached 150% in the year 1999